P126 Improving the management of antenatal women with positive syphilis serology within a genitourinary medicine service. (23rd May 2012) - Patel, S; Aroney, R; Bird, M; Rice, P; Hay, P
Abstract : Background: Congenital syphilis (STS) can be prevented through antenatal screening and treatment. The true incidence of congenital STS is unknown; ∼10 cases/yr have been reported to the HPA by GUM clinics (probably reflects 30%–50% of cases). An audit at our centre (∼5000 deliveries/yr) in 2004, highlighted suboptimal management of pregnant women with positive STS serology. Methods: A pathway has subsequently been developed and we report our findings since June 2004. Antenatal screening results are reviewed by a multidisciplinary team (MDT: virology, GU, antenatal, paediatric) experienced in the management of syphilis. Our GU team manages all pregnant women with positive serology who undergo full evaluation (incl. an STI check), further tests or treatment as necessary and follow-up of the neonate. Results: 123 referrals (108 pregnant women with positive STS serology) were received by the GU department from June 2004 to December 2009. Of these referrals, 36% (44) had STS (1 primary, 1 secondary, 6 early latent, 36 late latent), 37% (46) were previously treated, and 27% (33) were biological false positives. Those with untreated STS—median age 30 (IQR 26–35); ethnicity: 45% (20) black African, 23% (10) black Caribbean, 18% (8) white other, 9% (4) Asian, 2% (1) black British, 2% (1) white British. All women attended the GU clinic for treatment and follow-up; with one exception who remained untreated (late latent STS) and was repatriated prior to delivery to Uganda in 2004. GU screens identified Chlamydia (3), TV (2), warts (2), herpes (1), BV (6), thrush (5) and hepatitis B (4) in those with untreated STS. Discussion: Our innovative MDT approach where each positive antenatal STS result is managed by our GU team has resulted in prompt treatment of untreated cases, identification of untreated STIs, and no reported cases of congenital STS. Our effective robust pathway includes standardised communication with all relevant teams and we encourage its use nationally.